Teologiese opleiding tydens die Reformasie - Balzer, H. R. (Hervormde teologiese studies, 1994)
Theological training during the Reformation The profound changes in theological education during and after the Reformation are interpreted in the light of the new soteriology of Martin Luther, Philipp Melanchthon, and their followers. A comparison with the humanistic movement reveals the specifically theological character of education in that time. Salvation was no longer directly administered by the church, but communicated thrgugh the study of the Bible as witness. Finally, the article points to the importance of the heritage of this movement for theological education in today’s cultural and religious situation.